Burden of infection in Australian infants. (23rd September 2020) - Rowland, Rebecca; Sass, Zia; Ponsonby, Anne‐Louise; Pezic, Angela; Tang, Mimi LK; Vuillermin, Peter; Gray, Lawrence; Burgner, David; ,
Abstract : Aim: To determine the incidence, risk factors and health service utilisation for infection in the first 12 months of life in a population‐derived Australian pre‐birth cohort. Methods: The Barwon Infant Study is a population‐derived pre‐birth cohort with antenatal recruitment ( n = 1074) based in Geelong, Victoria, Australia. Infection data were collected by parent report, and general practitioner and hospital records at 1, 3, 6, 9 and 12 months of age. We calculated the incidence of infection, attendance at a health service with infection and used multiple negative binomial regression to investigate the effects of a range of exposures on incidence of infection. Results: In the first 12 months of life, infections of the upper and lower respiratory tract (henceforth 'respiratory infections'), conjunctivitis and gastroenteritis occurred at a rate of 0.35, 0.04 and 0.04 episodes per child‐month, respectively. A total of 482 (72.4%) infants attended a general practitioner with an infection and 69 (10.4%) infants attended the emergency department. Maternal antibiotic exposure in pregnancy and having older siblings were associated with respiratory infection. Childcare attendance by 12 months of age was associated with respiratory infections and gastroenteritis. Breastfeeding, even if less than 4 weeks in total, was associated with reduced respiratory infection. Conclusion: Infection, especially of the respiratory tract, is a common cause of morbidity in Australian infants. Several potentially modifiable risk factors were identified, particularly for respiratory infections. Most infections were managed by general practitioners and 1 in 10 infants attended an emergency department with infection in the first year of life.